Improved fixation in cementless unicompartmental knee replacement: five-year results of a randomized controlled trial. - Pandit, H; Liddle, A; Kendrick, B; Jenkins, C; Price, A; Gill, H; Dodd, C; Murray, D (Journal of Bone and Joint Surgery Inc., 2013)
BACKGROUND: When used for appropriate indications, unicompartmental knee replacement is associated with fewer complications, faster recovery, and better function than total knee replacement. However, joint registries demonstrate a higher revision rate for unicompartmental knee replacement. Currently, most unicompartmental knee replacements are cemented; common reasons for revision include aseptic loosening and pain. These problems could potentially be addressed by using cementless implants, with coatings designed to improve fixation. The objectives of this study were to compare the quality of fixation as well as clinical outcomes of cemented and cementless unicompartmental knee replacements at five years of follow-up. METHODS: A randomized controlled trial was established with sixty-three knees (sixty-two patients) receiving either cemented (thirty-two patients) or cementless Oxford unicompartmental knee replacements (thirty patients). Fixation was assessed with fluoroscopic radiographs aligned to the bone-implant interface at one and five years. Outcome scores, including the Oxford Knee Score, Knee Society objective and functional scores, and Tegner Activity Score, were collected preoperatively and at six months and one, two, and five years postoperatively. At each postoperative time point, these were recorded as absolute scores and change from the preoperative score. RESULTS: Four patients died during the study period. There were no revisions. Mean operative time was nine minutes shorter in the cementless group (p = 0.049). At five years, there was no significant difference in any outcome measure except the Knee Society functional score and the change in the Knee Society functional score, which were significantly better in the cementless group (p = 0.003 for both). There were significantly more tibial radiolucencies in the cemented group (twenty of thirty knees versus two of twenty-seven knees; p < 0.001). There were nine complete radiolucencies in the cemented group and none in the cementless group (p = 0.01). CONCLUSIONS: Cementless fixation provides improved fixation at five years compared with cemented fixation in mobile-bearing unicompartmental knee replacements, maintaining equivalent or superior clinical outcomes with a shorter operative time and no increase in complications. LEVEL OF EVIDENCE: Therapeutic level I. See Instructions for authors for a complete description of levels of evidence.